Cigarette butt filter as membrane material with tannic acid and FeCl3 additives for improve antifouling properties - Anisa Luthfiana; Sri Mulyati; Nasrul Arahman; Muhammad Roil Bilad; Muhammad Prayogie Aulia (Case Studies in Chemical and Environmental Engineering)
Membrane fouling remains a critical challenge in wastewater treatment, particularly in applications involving oil-water emulsions. This study addresses this issue by fabricating antifouling membranes from repurposed cigarette filter waste, modified with tannic acid and FeCl3 (ferric chloride) coatings. These modifications enhance membrane hydrophilicity, antifouling properties, flux recovery, and selectivity through an environmentally friendly approach. The membranes were prepared using the non-solvent induced phase separation (NIPS) method and subsequently coated through vacuum filtration. Key performance metrics included pure water flux, oil emulsion selectivity, and antifouling properties. The antifouling mechanism was attributed to the hydrophilic and protective layers formed by the tannic acid and FeCl3 modifications, which reduced fouling and improved flux recovery. Characterization revealed that the tannic acid and FeCl3 modifications created a hydrophilic layer with uniform pore distribution, leading to an oil rejection rate of up to 97 % and an increased flux recovery ratio of 85 %, compared to 65 % in unmodified membranes. The results highlight the potential of waste-derived membranes as a sustainable alternative for industrial wastewater treatment, aligning with the principles of circular economy and green chemistry. Future work should explore long-term stability, surface charge effects, and optimization of additive concentrations to enhance performance and antifouling efficiency further.